Building the climate change resilience of Mongolia blue pearl the case study of Khuvsgul Lake National Park. - Bezuijen, Mark R. (Asian Development Bank, 2020)
This publication presents the first quantitative assessment of the impact of climate change on a protected area in Mongolia and helps identify adaptation measures to build climate resilience for biodiversity conservation, livelihoods, and tourism.Climate change threatens to undermine the ecological values provided by protected areas, such as the Khuvsgul Lake National Park one of the largest and most visited parks in Mongolia. Known locally as the sacred Blue Pearl to Mongolians, Khuvsgul Lake has environmental and economic benefits that are equally important. This publication emphasizes that building resilience to climate change is critical and requires collaboration and coordination between national and international agencies to promote sustainable practices in the protected areas.